Bears in the scene: Pleistocene complex interactions with implications concerning the study of Neanderthal behavior. (12th April 2017) - Camarós, E.; Cueto, M.; Teira, L.; Münzel, Susanne C.; Plassard, F.; Arias, P.; Rivals, F.
Abstract: The evidence of modern and complex behavior is a key debate in human evolution. Neanderthals have been excluded from this debate from many years, until new insight have provided a new conception of the Neanderthal behavior. Nevertheless, although archaeological data of complex and modern behavior has been inferred, this is not a generalized scenario in Middle Paleolithic sites. In the present paper, we point taphonomical issues as the responsible for this misconservation of cognitive markers. Furthermore, we highlight the action of ursids as one of the agents that has most modified the archaeological record. Nevertheless, bears not just erase behavioral evidences, their action may also generate material realities that can be misinterpreted by archaeologist as Neanderthal behavioral markers. In the present paper we analyze issues related to organized use of space and symbolic behavior such as inhumation practices and graphical expression. We approach this issue from a multidisciplinary research based mainly in actualistic, experimental, paleontological and ethological observations.